Tributaries of West Antarctic Ice Streams Revealed by RADARSAT Interferometry - Joughin, I.; Gray, L.; Bindschadler, R.; Hulbe, C.; Price, S.; Mattar, K.; Werner, C. (2004)
Interferometric RADARSAT data are used to map ice motion in the source areas of four West Antarctic ice streams.